Unusual groups of Morganella ("Proteus") morganii isolated from clinical specimens: lysine-positive and ornithine-negative biogroups. - Hickman, F W (1980)
Morganella ("Proteus") morganii is the only species in the recently proposed genus Morganella, but we suspect there are yet undescribed species in the genus. Two candidates for new species were recently investigated. Nineteen strains isolated from clinical specimens resembled M. morganii but were lysine positive and nonmotile and fermented glycerol within 24 h. Typical M. morganii are lysine negative and motile and ferment glycerol slowly or not at all. The three-test variance from typical M. morganii suggested that this new group might be a new Morganella species; however, strains of the group were closely related to typical M. morganii by deoxyribonucleic acid (DNA)-DNA hybridization. A second group of 14 strains isolated from clinical specimens was ornithine negative but was otherwise very similar to M. morganii. This group was also closely related to M. morganii by DNA hybridization. Both sets of strains clearly belong in the species Morganella morganii as distinct biogroups; they are not separate species as originally suspected. Initially both biogroups posed a problem in identification until their true relationship to M. morganii was determined.